An improved Environmental Impact Assessment (EIA) process in Malaysia towards sustainable development / Maisarah Makmor - Makmor, Maisarah (2014)
Environmental Impact Assessment (EIA) is defined as a planning tool to identify, predicts and evaluate potential environmental impacts and mitigation measures in early stages of proposed projects. This research aims to establish an improved EIA process in Malaysia towards sustainable development. Three objectives which are to recognise the fundamentals of EIA process and procedures applied in Malaysia, to analyse the factors of approval and rejection of EIA reports submitted to the Department of Environment Malaysia and to propose a set of recommendations to further improve the current EIA process in Malaysia are utilised to achieve the aim of research. Although EIA has been implemented in Malaysia for over 25 years, the EIA practices have yet to achieve the parameters of effective environmental management and sustainable development. This research embarked mixed methods approach were the qualitative data were collected via document review and semi-structured interviews while quantitative data was gathered utilising questionnaire survey. Eleven EIA reports were reviewed and twenty five respondents participated in the semistructured interviews and data were analysed via NvivolO software. Qualitative analyses indicated that low stakeholder engagement, deficiency in capacity building in DOE, lack of coordination between agencies, structure and input of the EIA reports, lack of awareness on the importance of EIA and credibility of consultants are the key issues on the EIA process in Malaysia. Recommendations on the issues were contextualised and a validation survey was conducted to twenty five respondents to validate the proposed recommendations for the improved EIA process. Ergo, an improved EIA process in Malaysia towards sustainable development was established to ameliorate the EIA practices in Malaysia